Bangkok Nightlife’s Destination Image Perception of Foreign Female Tourists - Wichaidit, Supaporn; Punyasiri, Sangkae (Journal of Business Administration The Association of Private Higher Education Institutions of Thailand, 2020)
The purpose of this research was 1) to study the level of foreign female tourists’ destination image perception of Bangkok’s nightlife, 2) to analyze Exploratory Factor Analysis (EFA) of foreign female tourists’ destination image perception of Bangkok’s nightlife, and 3) to propose a model of the influence of destination image of Bangkok’s nightlife perceived by international female tourists toward the behavioral intention under mediating effects of satisfaction. The samples of 400 respondents were used by accidental sampling technique in Bangkok nightlife areas. The result showed that nightlife destination image was divided into 11 aspects with difference level. Moreover, EFA result showed the difference of 4 groups of nightlife destination image including: 1. cultural environment and activities, 2. cuisine, 3. value and atmosphere, and 4. safety and security. The result also revealed that structural equation modeling of nightlife destination image had a significant effect on satisfaction and had indirectly affected toward behavioral intention under mediating effects of satisfaction at the significance level of 0.05.